2018
DOI: 10.5114/ada.2018.76224
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Chlamydophila pneumoniae DNA in blood cells is a frequent event in patients with the late stage of primary cutaneous lymphomas and with atopic dermatitis

Abstract: IntroductionMicrobial infection and associated super antigens have been implicated in the pathogenesis of cutaneous T-cell lymphoma (CTCL), and many patients die from complicating bacterial infections. It has been postulated that Chlamydophila pneumoniae (C. pneumoniae) infection may be involved in the pathogenesis of Mycosis fungoides (MF) but published data are limited and controversial.AimTo analyze the frequency of (C. pneumoniae) DNA presence in blood samples of lymphoma cases.Material and methodsUsing Q-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…While a number of studies failed to show any association with pathogenic organisms, studies concluding a definite infectious role in CTCL aetiology have also been reported [ 59 ]. Several researchers examined an association with Chlamydophila pneumonia [ 60 , 61 ] and Borrelia burgdorferi [ 62 , 63 ]. However, most of the studies of possible bacterial pathogenesis have focused on investigating the role of Staphylococcus aureus [ 64 , 65 ].…”
Section: Role Of Infectious Agents In Disease Onset and Progressiomentioning
confidence: 99%
“…While a number of studies failed to show any association with pathogenic organisms, studies concluding a definite infectious role in CTCL aetiology have also been reported [ 59 ]. Several researchers examined an association with Chlamydophila pneumonia [ 60 , 61 ] and Borrelia burgdorferi [ 62 , 63 ]. However, most of the studies of possible bacterial pathogenesis have focused on investigating the role of Staphylococcus aureus [ 64 , 65 ].…”
Section: Role Of Infectious Agents In Disease Onset and Progressiomentioning
confidence: 99%